PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AI UNTUK MENDUKUNG INOVASI PENDIDIKAN DI ERA DIGITAL - Mohammad Syahidul Haq; Ari Khusumadewi; Khesya Dyanza (Universitas Negeri Surabaya, 2026)
Teachers at MTs Miftahul Ulum Kemlagi experienced limitations in utilizing Artificial Intelligence (AI)-based learning media and had varying levels of digital competence, creating challenges in implementing innovative learning practices. This Community Service Program (PKM) aims to enhance the digital competence of teachers at MTs Miftahul Ulum Kemlagi through training in the development of AI-based learning media using the Gemini AI platform. The program employed a Participatory Action Research (PAR) approach consisting of material delivery, hands-on practice, continued mentoring, and evaluation. A total of 25 teachers participated in the training and demonstrated improved ability in designing AI-assisted learning media relevant to their instructional needs. The evaluation results indicated positive participant responses, with an average score of 3.02 categorized as good, reflecting the practicality, clarity, and applicability of the training program. Beyond improving technical skills, the program encouraged teacher engagement and strengthened readiness to adopt digital innovation in the madrasah environment. Thus, the integration of AI, particularly through Gemini AI, demonstrates significant potential in supporting creative, contextual, and future-oriented Islamic education practices in the madrasah setting.